STRATEGIES FOR EFFECTIVE URBAN SOLID WASTE MANAGEMENT IN NIGERIA - Uwadiegwu, B. O.; Chukwu, K. E. (European Scientific Journal, ESJ, 2013)
The aim of this paper is to proffer urban solid waste management strategies which will effectively address the problems emanating from solid waste management. Three layouts in Enugu city. Namely, Independence Layout (low density), Idaw River (medium density) and Uwani (high density) were used for the study. 310 households selected randomly from these layouts participated as respondents. Principal Components Analysis (PCA) version of Factor Analysis was used to analyze the responses of respondents. The PCA was used to reduce the 27 considered management options into 7 composite strategies which should be adopted for effective urban solid waste management. They are citizen mobilization and environmental education, strengthening of public agencies, responsible government, logistics and infrastructural improvement, legislation, appropriate technologies, monitoring and surveillance. It is recommended that all segments of the society must team up with public agency to find a panacea to urban solid waste management.